Visualisasi Hasil Amplifikasi Dna Origin Kelapa Sawit (Elaeis Guineensis Jacq.) Plasma Nutfah PT. Socfindo Berdasarkan Tiga Primer SSR - Rini Anggreini; Eva Sartini Bayu; Hot Setiado (Jurnal Agroekoteknologi, 2019)
The oil palm plant is a one-piece plant included in Palmae's family. Molecular marking applications can be used to improve efficiency in analyzing genetic relationship, gene mapping, and marker-assisted selection (MAS) in oil palm plants. This study aims to determine the visualization of the amplification of DNA of Origin of Oil Palm (Elaeis guineensis Jacq.) Germplasm PT. Socfindo Based on Three SSR (Simple Sequence Repeats) Primers. The material analyzed is the 14 origin of oil palm originating from the germplasm of PT. Socfindo. The results showed the size of DNA bands that varied from 138 bp to 308 bp. The lowest band size was found on the FR-0782 primers, namely 138-211 bp and the polymorphic percentage was 60%. Key words: oil palm, molecular markers, SSR markers